The Extended Laguerre Polynomials Aq, nαx Involving Fqq, q>2. (15th April 2022) - Khan, Adnan; Kalim, Muhammad; Akgül, Ali; Jarad, Fahd
Abstract : In this paper, for the proposed extended Laguerre polynomials A α q, n x, the generalized hypergeometric function of the type F q q, q > 2 and extension of the Laguerre polynomial are introduced. Similar to those related to the Laguerre polynomials, the generating function, recurrence relations, and Rodrigue's formula are determined. Some corollaries are also discussed at the end.